2019
DOI: 10.1038/s41366-019-0483-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of new onset cardiometabolic risk among normal weight children

Abstract: Objective To identify determinants for the development of "normal weight metabolically unhealthy" (NWMU) profiles among previously metabolically healthy normal weight children. Methods The QUALITY cohort comprises youth 8-10 years of age with a parental history of obesity (n = 630). Of these, normal weight children with no metabolic risk factors were identified and followed up 2 years later (n = 193). Children were classified as NWMU if they remained normal weight but developed at least one cardiometabolic ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…One study of 8899 participants followed for 4 months linked higher fibre intake to a decreased frequency of hard stools 44 . Higher vegetable and fruit intake as a composite marker was associated with a decrease in school grades in 334 children, 45 but not becoming ‘normal‐weight metabolically unhealthy’ 46 . Two 47,48 of three studies with 2554 participants identified decreased incidence of metabolic syndrome with higher vegetable intake, with the third study providing a non‐significant odds ratio of 0.95 (95% CI 0.85 to 1.04) 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of 8899 participants followed for 4 months linked higher fibre intake to a decreased frequency of hard stools 44 . Higher vegetable and fruit intake as a composite marker was associated with a decrease in school grades in 334 children, 45 but not becoming ‘normal‐weight metabolically unhealthy’ 46 . Two 47,48 of three studies with 2554 participants identified decreased incidence of metabolic syndrome with higher vegetable intake, with the third study providing a non‐significant odds ratio of 0.95 (95% CI 0.85 to 1.04) 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Body weight [23][24][25][26][27][28][29]32,[69][70][71] Blood lipids 26,32 Glycaemia 32 Blood pressure 25,32,38 Metabolic syndrome 48,49 Bone health 41 Cognition 50,51 Vegetables and fruit 13 5286 Body weight 22,34,35,46,65,72 Blood lipids 33 Glycaemia 34 Blood pressure 36,73,74 Bone health 39,40 Cognition 45 Refined or whole grains 6 10 037 Body weight 26,27 Blood lipids 26,33 Glycaemia 67 Metabolic syndrome 49 Cognition 51 with a higher intake of fruit 50,51 ; however, these benefits were not observed with higher vegetable or wholegrain intakes. 51…”
Section: Fruit 17 22 216mentioning
confidence: 99%
“…A 2-month life style modi cation trial in 12-16-year olds, comprising aerobic activity classes, diet education and behaviour modi cation, reduced body fat mass and improved lipid pro le and in ammation [40]. Postulated mechanisms from observational evidence in adults and children also include greater relative fat accumulation, especially in the visceral adipose tissue, liver and upper body, inferior aerobic tness, lower skeletal muscle mass and strength, increased screen time and diet quality -lower fruits and vegetables -and higher fructose and glucose intakes [13,41,42]. Mechanisms underlying a similar phenomenon in thin (underweight) subjects have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between WHtR, BMI, WC and WHR have been previously reported by various studies. [6,[8][9][10][11]20] Neck circumference as an indicator of cardiometabolic risk has also been reported, [21][22][23] but it is relatively recent and an emerging topic which should be better explored.…”
Section: Discussionmentioning
confidence: 99%